Screening of Secondary Metabolite Compounds of Gorontalo Traditional Medicinal Plants Using the In Silico Method as a Candidate for SARS-CoV-2 Antiviral - Yuszda K. Salimi; La Ode Aman; Zaenul Wathoni; Netty Ino Ischak; Akram La Kilo; La Alio (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
COVID-19 is a disease that caused a prolonged pandemic in many countries caused by the SARS-CoV-2 virus. This study aims to identify the antiviral potential of secondary metabolites in Gorontalo traditional medicinal plants, which are believed to have the ability to inhibit the main protease protein of this virus. The methods used in this research were molecular docking and molecular dynamic. The main protease proteins for SARS-CoV-2 used based on the homology modeling results were 3V3M and 7TE0. The results of the active compounds in the paxlovid drug were also compared to obtain accurate data comparisons. The validation of the docking method on the 3V3M protein using the natural ligand 0EN revealed an RMSD of 0.75 Å. The RMSD value for validating the 7TE0 protein and natural ligand 4WI was 1.65 Å. The best molecular docking results were obtained using physalin F with a binding affinity of −10.3 kcal/mol for the 3V3M protein and physalin J with a binding affinity of −8.9 kcal/mol for the 7TE0 protein. The outcomes of the molecular dynamic method on the best complexes were determined by examining the value of changes in system energy, changes in system temperature, changes in system pressure, RMSD, RMSF, and bond-free energy (ΔG) of the complex. The standard 0EN ligand had a ΔG of −26.53 kcal/mol, while the standard 4WI ligand had a ΔG of −47.16 kcal/mol. The ΔG of the 3V3M-physalin F and 3V3M-physalin J complexes were respectively −28.22 kcal/mol and −26.62 kcal/mol. The ΔG of the 7TE0-Vitexin 2”-O-gallate and 7TE0-physalin J complexes were found to be −28.08 kcal/mol and −26.62 kcal/mol, respectively. The ΔG produced in paxlovid with complexes 3V3M and 7TE0 was −19.38 kcal/mol and −25.44 kcal/mol, respectively. Physalin F, physalin J, and Vitexin 2”-O-gallate have great potential to become SARS-CoV-2 inhibitor agents. However, in terms of structural stability and binding-active residues, these three compounds do not outperform the active substance in paxlovid.